The relationship between the history of infectious diseases and the incidence Stunting in toddlers aged 0-59 months: A literature review - Nabila Maulidiana Putri; Hermiaty Nasruddin; A. Sastri Zainuddin; Sidrah Darma; Andi Tenrigangka (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Stunting is a chronic nutritional problem among toddlers and remains a major public health concern. A history of infectious diseases is considered an important factor contributing to stunting. Purpose: This study aimed to review the association between infectious disease history and stunting in toddlers through a literature review. Method: A total of 25 national and international research articles were analyzed, most of which used case-control and cross-sectional designs. Results: The findings show that the majority of studies reported a significant association between infectious diseases particularly diarrhea, Acute Respiratory Infections (ARI), and intestinal parasitic infections and stunting (p < 0.05), with a 2–7 times higher risk. Longer duration and recurrent infections increase the risk of stunting by impairing nutrient absorption. However, several studies reported no significant association due to differences in respondent characteristics and confounding factors. Conclusion: Overall, stunting is a multifactorial condition requiring comprehensive prevention strategies.